Thin film for semiconductor laser bonding and manufacturing method thereof

JP2025031284APending Publication Date: 2025-03-07CITIZEN FINEDEVICE CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023137407
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-25
Publication Date
2025-03-07

AI Technical Summary

Benefits of technology

【0016】 本発明に係る半導体レーザ接合用薄膜は、高性能化及び低融点化が可能である。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025031284000001_ABST
    Figure 2025031284000001_ABST
Patent Text Reader

Abstract

To provide a thin film for semiconductor laser bonding that can improve performance and reduce melting points.SOLUTION: A thin film 1 for semiconductor laser bonding has a solder layer 40 containing 7.2 wt.% or more and 14.0 wt.% or less of Au, 0.1 wt.% or more and 4.4 wt.% or less of Ag, 0.1 wt.% or more and 10.1 wt.% or less of Cu, and the remainder being Sn except for unavoidable impurities.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a thin film for semiconductor laser bonding and a method for producing the same. [Background technology]

[0002] Various techniques are known for improving the performance of thin solder films used when mounting light-emitting elements such as laser diodes on submount substrates. For example, Non-Patent Document 1 describes a thin solder film that does not use flux, which may degrade the performance of light-emitting elements. The thin solder film described in Non-Patent Document 1 has an Ag layer disposed between an Sn layer and an Au layer, which prevents Au contained in the Au layer from diffusing into the Sn layer, and can prevent poor wetting and Kirkendall voids caused by surface oxidation.

[0003] Patent Document 1 also describes a thin solder film in which an Ag layer and a Cu layer are arranged between three Sn layers, and the Ag content is 5.5% by weight or less, the Cu content is 1.5% by weight or less, and the Sn content is 93.0% by weight or more. The thin solder film described in Patent Document 1 is bonded to an Au electrode to form a SnAgCuAu alloy, which realizes a melting point of 250°C or less. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2007-288001 A [Non-patent literature]

[0005] [Non-Patent Document 1] "Development of low melting point Sn-based thin film solder for fluxless connection", Sakamoto et al., Journal of the Japan Institute of Electronics Packaging, Vol. 14, No. 3, 2011, p. 179-188 Summary of the Invention [Problem to be solved by the invention]

[0006] The solder thin film described in Non-Patent Document 1 can suppress poor wetting and the occurrence of voids, and the solder thin film described in Patent Document 1 can achieve a melting point of 250°C or less, but there is a demand for thin films for semiconductor laser bonding with even higher performance and lower melting points.

[0007] The present invention is intended to solve these problems, and provides a thin film for semiconductor laser bonding that allows for high performance and a low melting point. [Means for solving the problem]

[0008] The thin film for semiconductor laser bonding according to the present invention has a solder layer containing 7.2% by weight or more and 14.0% by weight or less of Au, 0.1% by weight or more and 4.4% by weight or less of Ag, 0.1% by weight or more and 10.1% by weight or less of Cu, and the remainder being Sn except for unavoidable impurities.

[0009] Furthermore, in the semiconductor laser bonding thin film according to the present invention, Cu preferably forms a Cu layer disposed over the entire surface of one side of the solder layer.

[0010] Furthermore, the semiconductor laser bonding thin film according to the present invention preferably contains Au at 7.2 wt % or more and 14.0 wt % or less.

[0011] Furthermore, the thin film for semiconductor laser bonding according to the present invention preferably contains 0.1% by weight or more and 4.4% by weight or less of Ag, and 0.1% by weight or more and 6.7% by weight or less of Cu.

[0012] Furthermore, the semiconductor laser bonding thin film according to the present invention preferably contains 0.1% by weight to 10.1% by weight of Cu and 0.1% by weight to 3.1% by weight of Ag.

[0013] Furthermore, the semiconductor laser bonding thin film according to the present invention preferably further comprises a diffusion prevention layer that contains Pt and is disposed so as to face the surface of the solder layer on which Cu is disposed.

[0014] Furthermore, in the semiconductor laser bonding thin film according to the present invention, the diffusion prevention layer preferably has a Cr layer containing Cr, and a Pt layer containing Pt and disposed between the Cr layer and the solder layer.

[0015] Furthermore, the present invention provides a method for manufacturing a thin film for semiconductor laser bonding, which has a solder layer containing 7.2% by weight or more and 14.0% by weight or less of Au, 0.1% by weight or more and 4.4% by weight or less of Ag, 0.1% by weight or more and 10.1% by weight or less of Cu, and the remainder consisting of Sn except for unavoidable impurities, and includes processes of forming a Cu layer, forming an Ag layer on the Cu layer, forming a Sn layer on the Ag layer, and forming an Au layer on the Sn layer. Effect of the Invention

[0016] The thin film for semiconductor laser bonding according to the present invention can achieve high performance and a low melting point. [Brief description of the drawings]

[0017] [Figure 1] 1A to 1C are diagrams showing a semiconductor laser bonding thin film according to a first embodiment. [Diagram 2] 1(a) is a diagram showing the reaction state between Cu contained in the Cu layer and Sn contained in the Sn layer when the semiconductor laser bonding thin film shown in FIG. 1 is heated, and FIG. 1(b) is a cross-sectional photograph of the semiconductor laser bonding thin film shown in FIG. 1 before and after it melts. [Diagram 3] FIG. 1 is a Sn-Ag-Cu phase diagram. [Figure 4] FIG. 1 is a Au-Sn phase diagram. [Diagram 5] 2A is a flowchart showing a method for manufacturing a semiconductor laser bonding thin film shown in FIG. 1, and FIG. 2B is a flowchart showing more detailed processing of step S104 shown in FIG. [Figure 6] 6A to 6C are diagrams showing a semiconductor laser bonding thin film according to a second embodiment. [Figure 7] 13A and 13B are diagrams showing a semiconductor laser bonding thin film according to a third embodiment. [Figure 8] 13A and 13B are diagrams showing a semiconductor laser bonding thin film according to a fourth embodiment. [Figure 9] (a) is a surface image of sample 1 during RTA treatment, (b) is an SEM image of a cross-section of sample 1 after RTA treatment, (c) is a surface image of sample 2 during RTA treatment, (d) is an SEM image of a cross-section of sample 2 after RTA treatment, (e) is a surface image of sample 3 during RTA treatment, (f) is an SEM image of a cross-section of sample 3 after RTA treatment, (g) is a surface image of sample 4 during RTA treatment, and (h) is an SEM image of a cross-section of sample 4 after RTA treatment. [Figure 10] (a) is a surface image of Example 1 during RTA treatment, (b) is an SEM image of a cross section of Example 1 after RTA treatment, (c) is a surface image of Example 2 during RTA treatment, (d) is an SEM image of a cross section of Example 2 after RTA treatment, (e) is a surface image of Example 3 during RTA treatment, (f) is an SEM image of a cross section of Example 3 after RTA treatment, (g) is a surface image of Example 4 during RTA treatment, (h) is an SEM image of a cross section of Example 4 after RTA treatment, (i) is a surface image of Example 5 during RTA treatment, and (j) is an SEM image of a cross section of Example 5 after RTA treatment. [Figure 11] (a) is a surface image of Example 6 during RTA treatment, (b) is a surface image of Example 7 during RTA treatment, (c) is a surface image of Example 8 during RTA treatment, (d) is a surface image of Example 9 during RTA treatment, (e) is a surface image of Comparative Example 1 during RTA treatment, (f) is a surface image of Comparative Example 2 during RTA treatment, (g) is a surface image of Comparative Example 3 during RTA treatment, (h) is a surface image of Comparative Example 4 during RTA treatment, (i) is a surface image of Comparative Example 5 during RTA treatment, and (j) is a surface image of Comparative Example 6 during RTA treatment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] Hereinafter, a semiconductor laser bonding thin film and a manufacturing method thereof according to an embodiment will be described with reference to the drawings. However, it should be noted that the technical scope of the present invention is not limited to the embodiments, but extends to the inventions described in the claims and their equivalents.

[0019] (Configuration and Function of Thin Film for Semiconductor Laser Bonding According to the First Embodiment) FIG. 1 is a diagram showing a semiconductor laser bonding thin film according to the first embodiment.

[0020] The semiconductor laser bonding thin film 1 is mounted on a submount substrate 10, and has an electrode layer 20, a diffusion prevention layer 30, and a solder layer 40. A light emitting element such as a laser diode is mounted on the solder layer 40 of the semiconductor laser bonding thin film 1.

[0021] The submount substrate 10 is an aluminum nitride (AlN) substrate having a rectangular planar shape and a thermal expansion coefficient smaller than that of metal, and the semiconductor laser bonding thin film 1 is disposed on the surface. The submount substrate 10 may be formed of ceramics other than AlN, such as silicon carbide (SiC). The electrode layer 20 of the submount substrate 10 has a wiring pattern, and is connected to the light emitting element mounted on the solder layer 40 via a bonding wire (not shown). Furthermore, the submount substrate 10 is mounted on a metal stem such as a CAN package, and is connected to the wiring pattern of the electrode layer and a lead disposed on the metal stem via a bonding wire.

[0022] The electrode layer 20 includes a titanium (Ti) layer 21, an electrode platinum (Pt) layer 22 laminated on the Ti layer 21, and an electrode gold (Au) layer 23 laminated on the electrode Pt layer 22. The electrode layer 20 has a wiring pattern and is connected to one electrode of the light-emitting element mounted on the solder layer 40 via a bonding wire (not shown). The Ti layer 21 is formed of Ti, the electrode Pt layer 22 is formed of Pt, and the electrode Au layer 23 is formed of Au. The Ti layer 21 and the electrode Pt layer 22 are diffusion prevention layers that prevent the diffusion of Au contained in the electrode Au layer 23, and the electrode Au layer 23 is a pad layer connected to the bonding wire. The Ti layer 21 also functions as an adhesive layer with the submount substrate 10.

[0023] The diffusion prevention layer 30 is made of Pt and is laminated on the electrode layer 20. The diffusion prevention layer 30 prevents tin (Sn) and Au contained in the solder layer 40 laminated on the diffusion prevention layer 30 from diffusing into the electrode layer 20. The thickness of the diffusion prevention layer 30 is preferably 0.01 μm or more and 0.6 μm or less, and more preferably 0.1 μm or more and 0.3 μm or less. When the thickness of the diffusion prevention layer 30 is thicker than 0.6 μm, burrs may be generated when forming a wiring pattern by a lift-off method or the like. Also, when the thickness of the diffusion prevention layer 30 is thinner than 0.01 μm, the effect of preventing diffusion cannot be sufficiently obtained.

[0024] The solder layer 40 has a copper (Cu) layer 41, a silver (Ag) layer 42, a Sn layer 43, and a Au layer 44, and melts when heated to a predetermined temperature, thereby mounting the light-emitting element to the submount substrate 10 via the electrode layer 20 and the diffusion prevention layer 30.

[0025] The Cu layer 41 is made of Cu and is disposed over the entire surface of one side of the solder layer 40 so as to face one side of the diffusion prevention layer 30. The Cu layer 41 is a layer for generating an appropriate intermetallic compound between the diffusion prevention layer 30 and the solder layer 40 when the solder layer 40 is heated. By disposing the Cu layer 41 over the entire surface of one side of the solder layer 40, the rate at which Cu is mixed into the Sn layer 43 can be suppressed, and the rise in the melting point of the solder layer 40 can be made gentler.

[0026] The Cu content in the solder layer 40 is preferably 0.1% by weight or more and 10.1% by weight or less. When the Cu content is less than 0.1% by weight, the reaction between the diffusion prevention layer 23 and the Sn layer 43 occurs early when the solder layer 40 is heated, and the melting duration, which is the time during which the solder layer 40 continues to be in a molten state, is significantly reduced. When the Cu content in the solder layer 40 is 0.1% by weight or more and 10.1% by weight or less, a large number of voids are not generated, and high reliability is possible. When the Cu content is more than 10.1% by weight, a large number of voids may be generated at the interface between the diffusion prevention layer 30 and the solder layer 40 when the solder layer 40 is heated.

[0027] 2(a) is a diagram showing the reaction state between Cu contained in the Cu layer 41 and Sn contained in the Sn layer 43 when the semiconductor laser bonding thin film 1 is heated, and FIG. 2(b) is a cross-sectional photograph of the semiconductor laser bonding thin film 1 before and after melting. In the solder layer 40, the Ag layer 42 is disposed between the Cu layer 41 and the Sn layer 43, but the content of Ag contained in the Ag layer 42 in the solder layer 40 is small, and even in the presence of the Ag layer 42, a reaction occurs between the Cu contained in the Cu layer 41 and the Sn contained in the Sn layer 43, and the effect of this reaction is large. Therefore, the reaction state will be described here without the Ag layer 42.

[0028] When the semiconductor laser bonding thin film 1 is heated, Cu reacts with Sn to form Cu 6 Sn 5is generated, the bond between the Cu layer 41 and the Sn layer 43 is strengthened, and as a result, the adhesion between the diffusion prevention layer 30 and the solder layer 40 is enhanced. 6 Sn 5 After the formation of Cu, the reaction between Cu and Sn occurs again, resulting in Cu 6 Sn 5 Instead of Cu 3 Sn is generated. Cu 6 Sn 5 While the amount of diffusion of Cu and Sn is almost the same during the generation of Cu, 3 When Sn is generated, the amount of Cu diffused is greater than the amount of Sn diffused, so that the Cu layer 41 and the Cu 3 The thickness of the Cu layer 41 and the Cu content of the solder layer 40 are 6 Sn 5 is generated, and Cu 3 It is adjusted so that Sn is not generated.

[0029] The Ag layer 42 is formed of Ag and is arranged so as to cover the entire upper surface of the Cu layer 41. By including Ag in the solder layer 40, the deterioration of the solder layer 40 due to a heat cycle test or the like is mitigated, and the reliability is improved. The Ag content in the solder layer 40 is preferably 0.1% by weight or more and 4.4% by weight or less. When the Ag content is less than 0.1% by weight, the effect of including Ag, that is, the reliability is improved, is not substantially realized. When the Ag content is 0.1% by weight or more and 4.4% by weight or less, the melting point can be lowered. FIG. 3 is a Sn-Ag-Cu phase diagram. The melting point reduction due to the inclusion of a small amount of Ag can be qualitatively explained by the Sn-Ag-Cu phase diagram. In FIG. 3, the horizontal axis indicates the Cu content in the Sn-Ag-Cu alloy, the vertical axis indicates the Ag content in the Sn-Ag-Cu alloy, and the numbers in the diagram indicate the melting point. It can be seen that the melting point increases as the Ag content increases above 4.5 wt. %. In solder layer 40, which contains Au from Au layer 44 in addition to Sn, Ag, and Cu and is also affected by the inclusion of Pt from diffusion prevention layer 30, when the Ag content is greater than 4.5 wt. %, the melting point of solder layer 40 exceeds 210° C., making it difficult to lower the melting point.

[0030] The Sn layer 43 is formed of Sn and is arranged so as to cover the entire upper surface of the Ag layer 42. Sn is the main component of the solder layer 40, and the Sn content in the solder layer 40 is preferably 83.1% by weight or more and 92.0% by weight or less, and more preferably 83.1% by weight or more and 88.7% by weight or less. The solder layer 40 is a low melting point solder mainly composed of Sn. AuSn (8:2 by weight) thin film solder, which is generally used for mounting laser diodes, has high reliability. However, AuSn (8:2 by weight) thin film solder has a high melting point of 278°C, and the thermal stress generated when mounting a laser diode may deteriorate the light emission characteristics of the laser diode, such as a blue shift of the emission wavelength and a decrease in light output due to the transition of the active layer. By using Sn as the main component of the solder layer 40, it is possible to lower the melting point, increase the ductility, and reduce stress.

[0031] The Au layer 44 is made of Au and is arranged to cover the entire upper surface of the Sn layer 43. The inclusion of a small amount of Au in the solder layer 40 allows the solder layer 40 to have a low melting point. FIG. 4 is an Au-Sn phase diagram. The fact that the melting point is lowered by the inclusion of a small amount of Au can be qualitatively explained by the Au-Sn phase diagram. From the Au-Sn phase diagram, it can be seen that in an Au-Sn alloy, when the Au content is less than 14.0% by weight, the melting point is approximately 240° C. or less. Therefore, it is preferable that the Au content in the solder layer 40 is 0.1% by weight or more and 14.0% by weight or less. When the Au content is less than 0.1% by weight, the effect of the inclusion of Au that allows the melting point to be lowered does not substantially appear. In the solder layer 40, which contains Sn, Ag, and Cu in addition to Au and is also affected by the Pt contamination of the diffusion prevention layer 30, when the Au content is 0.1% by weight or more and 14.0% by weight or less, the melting point of the semiconductor laser bonding thin film 1 becomes 210° C. or less, making it possible to lower the melting point. When the Au content is more than 14.0% by weight, the melting point of the semiconductor laser bonding thin film 1 becomes higher than 210° C., making it difficult to lower the melting point.

[0032] The remainder of the semiconductor laser bonding thin film 1 other than the above-mentioned component composition is made up of impurities. The impurities are components that are mixed in due to various factors in the manufacturing process when the semiconductor laser bonding thin film 1 is industrially manufactured, and are contained in an amount that does not affect the characteristics of the semiconductor laser bonding thin film 1.

[0033] When the solder layer 40 contains 7.2% to 14.0% by weight of Au, 0.1% to 4.4% by weight of Ag, 0.1% to 10.1% by weight of Cu, and the remainder, excluding unavoidable impurities, of Sn, it has suitable properties and is usable. By having such a composition, the solder layer 40 can have suitable properties such as a melting point of 210° C. or less, no large amount of voids being generated, and a melting duration of 5 seconds or more. Since optical elements such as semiconductor lasers are mounted within a few seconds after the solder melts, it is desirable for the melting duration to be 5 seconds or more.

[0034] It is more preferable that the Cu content in the solder layer 40 is 0.1% by weight or more and less than 10.1% by weight, and the Ag content in the solder layer 40 is 0.1% by weight or more and 3.1% by weight or less. When the Cu content in the solder layer 40 is 0.1% by weight or more and less than 10.1% by weight, and the Ag content in the solder layer 40 is 0.1% by weight or more and 3.1% by weight or less, there is no risk of voids being generated, and a lower melting point can be achieved, leading to further improved reliability. The decrease in melting point due to the inclusion of a small amount of Cu can be qualitatively explained by the Sn-Ag-Cu phase diagram shown in FIG. 3. It can be seen that when the Sn-Ag-Cu alloy contains a small amount of Cu, the smaller the Cu content, the lower the melting point.

[0035] It is more preferable that the Ag content is 0.1% to 3.1% by weight and the Cu content is 0.1% to 6.7% by weight in the solder layer 40. When the Ag content is 0.1% to 3.1% by weight and the Cu content is 0.1% to 6.7% by weight, a lower melting point is possible, no voids are generated, and high reliability is possible.

[0036] It is more preferable that the Au content in the solder layer 40 is 7.3% by weight or more and 14.0% by weight or less. When the Au content is 7.3% by weight or more and 14.0% by weight or less, the melting point of the semiconductor laser bonding thin film 1 becomes 205° C., and it is possible to further lower the melting point.

[0037] The content of Au in the solder layer 40 is preferably 7.3% by weight or more and 8.0% by weight or less, and more preferably 7.3% by weight or more and 7.7% by weight or less. When the content of Au is 7.3% by weight or more and 7.7% by weight or less, the melting duration is 15 seconds or more.

[0038] It is more preferable that the Ag content is 0.1% to 4.4% by weight and the Cu content is 0.1% to 6.7% by weight in the solder layer 40. When the Ag content is 0.1% to 4.4% by weight and the Cu content is 0.1% to 6.7% by weight, the melting point of the solder layer 40 becomes 205° C., making it possible to lower the melting point.

[0039] More preferably, the solder layer 40 contains 7.3% to 7.7% by weight of Au, 0.1% to 3.1% by weight of Ag, 0.5% to 6.7% by weight of Cu, and the remainder, excluding unavoidable impurities, of Sn. By having such a composition, the solder layer 40 can have further preferable properties, such as a melting point of 205°C, no generation of voids, and a melting duration of 15 seconds or more.

[0040] In addition, since Ag contained in the Ag layer 42 and Au contained in the Au layer 44 diffuse into the Sn layer 43 even at room temperature, the Ag layer 42, the Sn layer 43 and the Au layer 44 may be an integrated layer.

[0041] FIG. 5(a) is a flow chart showing a method for manufacturing the semiconductor laser bonding thin film 1.

[0042] First, in a substrate preparation step, an aggregate substrate is placed inside a vacuum chamber of a manufacturing apparatus (S101). The aggregate substrate is a flat plate-shaped member made of AlN that forms the submount substrate 10. After the aggregate substrate is placed inside the vacuum chamber, the inside of the vacuum chamber is evacuated.

[0043] Next, in an electrode layer formation step, the electrode layer 20 is formed (S102). The electrode layer 20 is formed by sequentially depositing a Ti layer 21, an electrode Pt layer 22, and an electrode Au layer 23 by a vacuum deposition process such as sputtering.

[0044] Next, in the diffusion prevention layer formation process, the diffusion prevention layer 30 is formed (S103). The diffusion prevention layer 30 is formed by depositing Pt on the electrode layer 20 by vacuum deposition, similar to the electrode layer formation process. Note that the area where the diffusion prevention layer 30 is not deposited is covered with a resist film.

[0045] Next, in the solder layer formation step, the solder layer 40 is formed on the diffusion prevention layer 30 (S104).

[0046] FIG. 5B is a flowchart showing the process of S104 in more detail.

[0047] First, in a Cu layer formation step, the Cu layer 41 is formed (S201). The Cu layer 41 is formed by depositing Cu on the diffusion prevention layer 30 by a vacuum deposition process. The thickness of the deposited Cu layer 41 is determined according to the content of Cu contained in the solder layer 40.

[0048] Next, in an Ag layer formation step, the Ag layer 42 is formed (S202). The Ag layer 42 is formed by depositing Ag on the Cu layer 41 by a vacuum deposition process. The thickness of the Ag layer 42 to be formed is determined according to the content of Ag contained in the solder layer 40.

[0049] Next, in a Sn layer formation step, the Sn layer 43 is formed (S203). The Sn layer 43 is formed by depositing Sn on the Ag layer 42 by a vacuum deposition process. The thickness of the Sn layer 43 to be formed is determined according to the content of Sn contained in the solder layer 40.

[0050] Then, in the Au layer formation step, the Au layer 44 is formed (S204). The Au layer 44 is formed by depositing Au on the Sn layer 43 by a vacuum deposition process. The thickness of the Au layer 44 to be formed is determined according to the content of Au in the solder layer 40.

[0051] Then, in the collective substrate cutting process, the collective substrate is cut (S105) to form a plurality of semiconductor laser bonding thin films 1, thereby completing the manufacturing process of the semiconductor laser bonding thin film 1. In the collective substrate cutting process, the resist film covering the electrode layer 20 is removed before cutting the collective substrate.

[0052] (Configuration and Function of Thin Film for Semiconductor Laser Bonding According to the Second Embodiment) FIG. 6 is a diagram showing a semiconductor laser bonding thin film according to the second embodiment.

[0053] The semiconductor laser bonding thin film 2 differs from the semiconductor laser bonding thin film 1 in that it has a diffusion prevention layer 31 instead of the diffusion prevention layer 30. The configurations and functions of the components of the semiconductor laser bonding thin film 2 other than the diffusion prevention layer 31 are the same as those of the components of the semiconductor laser bonding thin film 1 with the same reference numerals, and therefore detailed description thereof will be omitted here.

[0054] The diffusion prevention layer 31 has a chromium (Cr) layer 32 and a Pt layer 33. The Cr layer 32 is an adhesive layer that enhances the adhesion between the electrode layer 20 and the diffusion prevention layer 31. By disposing the Cr layer 32, even if the Pt layer 33 is completely consumed by a reaction with the solder layer 40, the electrode layer 20 and the solder layer 40 are not mixed with each other, and a sufficient diffusion prevention effect can be obtained. The film thickness of the Cr layer 32 is preferably 0.01 μm or more and 0.2 μm or less, and more preferably 0.03 μm or more and 0.1 μm or less. When the film thickness of the Cr layer 32 is thicker than 0.2 μm, there is a risk that peeling from the electrode layer 20 is induced by a strong stress of the Cr itself. Also, when the film thickness of the Cr layer 32 is thinner than 0.01 μm, a sufficient diffusion prevention effect is not substantially achieved.

[0055] The Pt layer 33 prevents Sn and Au contained in the solder layer 40 from diffusing into the electrode layer 20. The thickness of the Pt layer 33 is preferably 0.01 μm or more and 0.6 μm or less, and more preferably 0.1 μm or more and 0.3 μm or less.

[0056] The method for manufacturing the semiconductor laser bonding thin film 2 is similar to the method for manufacturing the semiconductor laser bonding thin film 1 except that it includes a step of laminating the diffusion prevention layer 31 on the electrode layer 20, so a detailed description thereof will be omitted here.

[0057] (Configuration and Function of Thin Film for Semiconductor Laser Bonding According to the Third Embodiment) FIG. 7 is a diagram showing a semiconductor laser bonding thin film according to the third embodiment.

[0058] The semiconductor laser bonding thin film 3 differs from the semiconductor laser bonding thin film 1 in that it has a solder layer 45 instead of the solder layer 40. The configurations and functions of the components of the semiconductor laser bonding thin film 3 other than the solder layer 45 are the same as those of the components of the semiconductor laser bonding thin film 1 with the same reference numerals, and therefore detailed description thereof will be omitted here.

[0059] Solder layer 45 differs from solder layer 40 in that solder layer 45 has a first Au layer 46 and a second Au layer 47 instead of Au layer 44. The configurations and functions of the components of solder layer 45 other than the first Au layer 46 and the second Au layer 47 are the same as the configurations and functions of the components of solder layer 40 with the same reference numerals, and therefore detailed description thereof will be omitted here.

[0060] The first Au layer 46 and the second Au layer 47 are formed of Au. The first Au layer 46 is disposed between the Ag layer 42 and the Sn layer 43, and the second Au layer 47 is disposed on the upper surface of the Sn layer 43, similar to the Au layer 44. The first Au layer 46 and the second Au layer 47 are disposed such that the total amount of Au contained in the first Au layer 46 and the second Au layer 47 is such that the content of Au in the solder layer 45 is 0.1% by weight or more and 14.0% by weight or less. The first Au layer 46 is disposed between the Ag layer 42 and the Sn layer 43, but may be disposed between the Cu layer 41 and the Ag layer 42.

[0061] The manufacturing method of the semiconductor laser bonding thin film 3 is similar to the manufacturing method of the semiconductor laser bonding thin film 1 except that it includes a step of laminating the first Au layer 46 between the Ag layer 42 and the Sn layer 43, so a detailed explanation is omitted here.

[0062] (Configuration and Function of Semiconductor Laser Bonding Thin Film According to the Fourth Embodiment) FIG. 8 is a diagram showing a semiconductor laser bonding thin film according to the fourth embodiment.

[0063] The semiconductor laser bonding thin film 4 differs from the semiconductor laser bonding thin film 2 in that it does not have an electrode layer 20. The Cr layer 32 of the diffusion prevention layer 31, which is an adhesion layer, adheres to the sub-mount substrate 10, so that the semiconductor laser bonding thin film 4 adheres to the sub-mount substrate 10.

[0064] The method for manufacturing the semiconductor laser bonding thin film 4 is similar to the method for manufacturing the semiconductor laser bonding thin film 1 except that the electrode layer forming step is not included, so a detailed description thereof will be omitted here.

[0065] (Layer structure of diffusion prevention layer and solder layer) Table 1 shows the layer configuration of the Sn layer, the diffusion prevention layer disposed under the Au layer disposed on the Sn layer, and the layer under the solder layer. In each of samples 1 to 4 shown in Table 1, a 3.0 μm-thick Sn layer is laminated on a lower layer laminated on an AlN substrate, and a 0.16 μm-thick Au layer is laminated on the Sn layer in this order.

[0066] [Table 1]

[0067] In Table 1, the column "Layer structure of lower layers" indicates the layer structure of the layers below the Sn layer and the Au layer, "First layer" indicates the bottom layer, "Second layer" indicates the layer stacked on the "First layer," "Third layer" indicates the layer stacked on the "Second layer," and "Fourth layer" indicates the layer stacked on the "Third layer."

[0068] The "meltability" column shows the meltability when subjected to rapid thermal annealing (RTA) at 220°C. In the RTA treatment, a pulse heater manufactured by Ichinohe Manufacturing Co., Ltd. was used to raise the temperature to 220°C within a few seconds and maintain the temperature for 20 seconds. In the "meltability" column, "〇" indicates that the molten state continued for 15 seconds or more when the sample was heated at 220°C, and "×" indicates that the molten state continued for less than 1 second when the sample was heated at 220°C. The "void" column shows the state of void generation when subjected to RTA treatment at 220°C. In the "void" column, "〇" indicates that no voids were generated, "△" indicates that a small amount of voids were generated, and "×" indicates that a large amount of voids were generated. The "evaluation" column is a comprehensive evaluation combining meltability and voids. In the "evaluation" column, "〇" indicates that it is good, and "×" indicates that it is bad.

[0069] Sample 1 has a Cr layer with a thickness of 0.05 μm as the first layer, a nickel (Ni) layer with a thickness of 0.20 μm as the second layer, a Sn layer with a thickness of 3.0 μm laminated on the Ni layer, and a Au layer with a thickness of 0.16 μm laminated on the Sn layer, in that order.

[0070] FIG. 9(a) is a surface image of sample 1 during the RTA treatment, and FIG. 9(b) is a scanning electron microscope (SEM) image of a cross section of sample 1 after the RTA treatment.

[0071] For sample 1, the molten state continued for less than 1 second during the RTA treatment, and a large number of voids were generated after the RTA treatment, so the sample was marked as "X" in both the "Meltability" and "Voids" columns, and also marked as "X" in the "Evaluation" column.

[0072] In sample 2, a Ti layer with a thickness of 0.05 μm is arranged as the first layer, a Pt layer with a thickness of 0.20 μm is arranged as the second layer, a Sn layer with a thickness of 3.0 μm is laminated on the Pt layer, and a Au layer with a thickness of 0.16 μm is laminated on the Sn layer.

[0073] FIG. 9(c) is a surface image of sample 2 during the RTA treatment, and FIG. 9(d) is an SEM image of the cross section of sample 2 after the RTA treatment.

[0074] For sample 2, no voids were generated after the RTA treatment, and the "Void" column was marked as "Good", but the molten state continued for less than 1 second during the RTA treatment, and the "Meltability" column was marked as "Poor", and the "Evaluation" column was marked as "Poor".

[0075] Sample 3 has a Ti layer with a thickness of 0.05 μm as the first layer, a Pt layer with a thickness of 0.20 μm as the second layer, and an Ag layer with a thickness of 0.74 μm as the third layer. A Sn layer with a thickness of 3.0 μm is laminated on the Ag layer, and a Au layer with a thickness of 0.16 μm is laminated on the Sn layer in this order.

[0076] FIG. 9(e) is a surface image of sample 3 during the RTA treatment, and FIG. 9(f) is an SEM image of the cross section of sample 3 after the RTA treatment.

[0077] For sample 3, the molten state continued for 15 seconds or more during the RTA treatment, and the "Meltability" column was marked "O". However, a large number of voids were generated after the RTA treatment, and the "Void" column was marked "X", and the "Evaluation" column was marked "X".

[0078] Sample 4 has a layer structure corresponding to the semiconductor laser bonding thin film 2. Sample 4 has a Cr layer with a thickness of 0.05 μm arranged as the first layer, a Pt layer with a thickness of 0.20 μm arranged as the second layer, a Cu layer with a thickness of 0.1 μm arranged as the third layer, and an Ag layer with a thickness of 0.74 μm arranged as the fourth layer. A Sn layer with a thickness of 3.0 μm is laminated on the Ag layer, and a Au layer with a thickness of 0.16 μm is laminated on the Sn layer in this order.

[0079] FIG. 9(g) is a surface image of sample 4 during the RTA treatment, and FIG. 9(f) is an SEM image of the cross section of sample 4 after the RTA treatment.

[0080] In sample 4, a small amount of voids were generated after the RTA treatment, and the "void" column was marked "△", but the molten state continued for 15 seconds or more in the RTA treatment, and the "meltability" column was marked "◯" and the "evaluation" column was marked "◯". The difference between sample 4 and sample 3 is whether a Pt layer is disposed between the Cr layer and the Cu layer, and the amount of voids generated in sample 4 is reduced by disposing a Pt layer. Sample 4 has a layer structure similar to that of the semiconductor laser bonding thin film 4. However, the effect of the layer structure in sample 4 is exerted in the semiconductor laser bonding thin films 1 to 3 in the same manner as in the semiconductor laser bonding thin film 4. EXAMPLES

[0081] (Au, Sn, Ag and Cu content in the solder layer) Table 2 shows the contents of Au, Sn, Ag and Cu in the solder layer. Each of Examples 1 to 9 and Comparative Examples 1 to 6 shown in Table 2 is formed by sequentially laminating a Cu layer, an Ag layer, a Sn layer and an Au layer on a diffusion prevention layer made of a Cr layer and a Pt layer laminated on a sub-mount substrate made of AlN. Each of Examples 1 to 9 and Comparative Examples 1 to 6 has a layer structure similar to that of the semiconductor laser bonding thin film 4. However, the effects of the contents of Au, Sn, Ag and Cu in the solder layer of Examples 1 to 9 and Comparative Examples 1 to 6 are exerted in the semiconductor laser bonding thin films 1 to 3 as well as in the semiconductor laser bonding thin film 4.

[0082] [Table 2]

[0083] In Table 2, the "Content" column indicates the content of Au, Sn, Ag, and Cu in the solder layer. The "Au" column indicates the Au content in the solder layer by weight%, the "Sn" column indicates the Sn content in the solder layer by weight%, the "Ag" column indicates the Ag content in the solder layer by weight%, and the "Cu" column indicates the Cu content in the solder layer by weight%.

[0084] The "Melting Point" column indicates whether the melting point was good or bad when RTA was performed. The RTA was performed by gradually increasing the temperature from room temperature to 240°C using a pulse heater manufactured by Ichinohe Manufacturing Co., Ltd. In the "Melting Point" column, "◯" indicates that the melting point was 205°C, "△" indicates that the melting point was 210°C, and "×" indicates that the melting point was higher than 210°C. The "Void" column indicates the occurrence of voids when RTA was performed at 220°C. In the "Void" column, "◯" indicates that no voids were generated, "△" indicates that a small amount of voids were generated, and "×" indicates that a large amount of voids were generated. The "Melting Duration" column indicates the time that the molten state continues when RTA was performed at 220°C. In the "Melting duration" column, "◯" indicates that the melted state continued for 15 seconds or more, "△" indicates that the melted state continued for 5 seconds or more but less than 15 seconds, and "×" indicates that the melted state continued for less than 5 seconds.

[0085] The "Evaluation Score" column is a score value for the overall evaluation combining melting property, voids, and melting duration. The values ​​shown in the "Evaluation Score" column are scored as follows: "O" in the "Melting Point", "Voids", and "Melting Duration" columns is scored as 2 points, "△" is scored as 1 point, and "X" is scored as 0 point. When the evaluation score is 6 points, the composition of the solder layer is considered to be in the optimal composition range. When the evaluation score is 5 points, the composition of the solder layer is considered to be in a composition range that is not optimal but usable. When the evaluation score is 4 points or less, the composition of the solder layer is considered to be in an unusable composition range.

[0086] Example 1 was formed by sequentially laminating Cu, Ag, Sn, and Au, and contains 8.0% by weight of Au, 91.8% by weight of Sn, 0.1% by weight of Ag, and 0.1% by weight of Cu.

[0087] FIG. 10(a) is a surface image of Example 1 during the RTA treatment, and FIG. 10(b) is an SEM image of a cross section of Example 1 after the RTA treatment.

[0088] In Example 1, the melting point was 205°C, so the "melting point" column was marked "○", no voids were generated after the RTA treatment, so the "void" column was marked "○", and the molten state continued for about 5 seconds, so the "melting duration" column was marked "△". Since the "melting point" column was marked "○", the "void" column was marked "○", and the "melting duration" column was marked "△", Example 1 was given an evaluation score of 5 points.

[0089] Example 2 was formed by sequentially laminating Cu, Ag, Sn, and Au, and contains 7.7% by weight of Au, 88.6% by weight of Sn, 3.1% by weight of Ag, and 0.5% by weight of Cu.

[0090] FIG. 10(c) is a surface image of Example 2 during the RTA treatment, and FIG. 10(d) is an SEM image of the cross section of Example 2 after the RTA treatment.

[0091] In Example 2, the melting point was 205°C, so the "melting point" column was marked "o", no voids were generated after the RTA treatment, so the "void" column was marked "o", and the molten state continued for 15 seconds or more, so the "melting duration" column was marked "o". Since the "melting point" column was marked "o", the "void" column was marked "o", and the "melting duration" column was marked "o", the evaluation score for Example 2 was 6 points.

[0092] Example 3 was formed by sequentially laminating Cu, Ag, Sn, and Au, and contains 7.6% by weight of Au, 87.5% by weight of Sn, 3.1% by weight of Ag, and 1.8% by weight of Cu.

[0093] FIG. 10(e) is a surface image of Example 3 during the RTA treatment, and FIG. 10(f) is an SEM image of the cross section of Example 3 after the RTA treatment.

[0094] In Example 3, the melting point was 205°C, so the "melting point" column was marked "o", no voids were generated after the RTA treatment, so the "void" column was marked "o", and the molten state continued for 15 seconds or more, so the "melting duration" column was marked "o". Since the "melting point" column was marked "o", the "void" column was marked "o", and the "melting duration" column was marked "o", the evaluation score for Example 3 was 6 points.

[0095] Example 4 was formed by sequentially laminating Cu, Ag, Sn, and Au, and contains 7.5% by weight of Au, 86.0% by weight of Sn, 0.3% by weight of Ag, and 3.5% by weight of Cu.

[0096] FIG. 10(g) is a surface image of Example 4 during the RTA treatment, and FIG. 10(h) is an SEM image of the cross section of Example 4 after the RTA treatment.

[0097] In Example 4, the melting point was 205°C, so the "melting point" column was marked "o", no voids were generated after the RTA treatment, so the "void" column was marked "o", and the molten state continued for 15 seconds or more, so the "melting duration" column was marked "o". Since the "melting point" column was marked "o", the "void" column was marked "o", and the "melting duration" column was marked "o", the evaluation score for Example 4 was 6 points.

[0098] Example 5 was formed by sequentially laminating Cu, Ag, Sn, and Au, and contains 7.3% by weight of Au, 83.1% by weight of Sn, 2.9% by weight of Ag, and 6.7% by weight of Cu.

[0099] FIG. 10(i) is a surface image of Example 5 during the RTA treatment, and FIG. 10(j) is an SEM image of the cross section of Example 5 after the RTA treatment.

[0100] In Example 5, the melting point was 205°C, so the "melting point" column was marked "o", no voids were generated after the RTA treatment, so the "void" column was marked "o", and the molten state continued for 15 seconds or more, so the "melting duration" column was marked "o". Since the "melting point" column was marked "o", the "void" column was marked "o", and the "melting duration" column was marked "o", the evaluation score for Example 5 was 6 points.

[0101] Example 6 was formed by sequentially laminating Cu, Ag, Sn, and Au, and contains 14.0% by weight of Au, 80.0% by weight of Sn, 2.8% by weight of Ag, and 3.2% by weight of Cu.

[0102] FIG. 11(a) is a surface image of Example 6 during the RTA treatment.

[0103] In Example 6, the melting point was 205°C, so the "melting point" column was marked "○", no voids were generated after the RTA treatment, so the "void" column was marked "○", and the molten state continued for about 5 seconds, so the "melting duration" column was marked "△". Since the "melting point" column was marked "○", the "void" column was marked "○", and the "melting duration" column was marked "△", Example 6 was given an evaluation score of 5 points.

[0104] Example 7 was formed by sequentially laminating Cu, Ag, Sn, and Au, and contains 7.7% by weight of Au, 88.6% by weight of Sn, 0.1% by weight of Ag, and 3.6% by weight of Cu.

[0105] FIG. 11(b) is a surface image of Example 7 during the RTA treatment.

[0106] In Example 7, the melting point was 205°C, so the "melting point" column was marked "○", no voids were generated after the RTA treatment, so the "void" column was marked "○", and the molten state continued for about 5 seconds, so the "melting duration" column was marked "△". Since the "melting point" column was marked "○", the "void" column was marked "○", and the "melting duration" column was marked "△", Example 7 was given an evaluation score of 5 points.

[0107] Example 8 was formed by sequentially laminating Cu, Ag, Sn, and Au, and contains 7.4% by weight of Au, 84.7% by weight of Sn, 4.4% by weight of Ag, and 3.4% by weight of Cu.

[0108] FIG. 11(c) is a surface image of Example 8 during the RTA treatment.

[0109] In Example 8, the melting point was 205°C, so the "melting point" column was marked "○", no voids were generated after the RTA treatment, so the "void" column was marked "○", and the molten state continued for about 5 seconds, so the "melting duration" column was marked "△". Since the "melting point" column was marked "○", the "void" column was marked "○", and the "melting duration" column was marked "△", Example 8 was given an evaluation score of 5 points.

[0110] Example 9 was formed by sequentially laminating Cu, Ag, Sn, and Au, and contains 7.2% by weight of Au, 82.7% by weight of Sn, 0.1% by weight of Ag, and 10.1% by weight of Cu.

[0111] FIG. 11(d) is a surface image of Example 9 during the RTA treatment.

[0112] In Example 9, the melting point was 210°C, so the "melting point" column was marked "△", no voids were generated after the RTA treatment, so the "void" column was marked "〇", and the molten state continued for 15 seconds or more, so the "melting duration" column was marked "〇". Since the "melting point" column was marked "〇", the "void" column was marked "〇", and the "melting duration" column was marked "△", the evaluation score for Example 9 was 5 points.

[0113] Comparative Example 1 was formed by sequentially laminating Cu, Ag, Sn, and Au, and contained 7.0% by weight of Au, 80.4% by weight of Sn, 2.8% by weight of Ag, and 9.8% by weight of Cu.

[0114] FIG. 11(e) is a surface image of Comparative Example 1 during the RTA treatment.

[0115] In Comparative Example 1, the melting point was 205°C, so the "melting point" column was marked "○", a large number of voids were generated after the RTA treatment, so the "void" column was marked "×", and the molten state continued for about 5 seconds, so the "melting duration" column was marked "△". Since the "melting point" column was marked "○", the "void" column was marked "×", and the "melting duration" column was marked "△", the evaluation score for Comparative Example 1 was 3 points.

[0116] Comparative Example 2 was formed by sequentially laminating Cu, Ag, Sn, and Au, and contained 6.8% by weight of Au, 77.8% by weight of Sn, 2.7% by weight of Ag, and 12.6% by weight of Cu.

[0117] FIG. 11(f) is a surface image of Comparative Example 2 during the RTA treatment.

[0118] In Comparative Example 2, the melting point was 205°C, so the "melting point" column was marked "○", a large number of voids were generated after the RTA treatment, so the "void" column was marked "×", and the molten state continued for about 5 seconds, so the "melting duration" column was marked "△". Since the "melting point" column was marked "○", the "void" column was marked "×", and the "melting duration" column was marked "△", the evaluation score for Comparative Example 2 was 3 points.

[0119] Comparative Example 3 was formed by sequentially laminating Cu, Ag, Sn, and Au, and contained 6.6% by weight of Au, 77.5% by weight of Sn, 2.7% by weight of Ag, and 15.3% by weight of Cu.

[0120] FIG. 11(g) is a surface image of Comparative Example 3 during the RTA treatment.

[0121] In Comparative Example 3, the melting point was 205°C, so the "melting point" column was marked "◯", a large number of voids were generated after the RTA treatment, so the "void" column was marked "X", and the molten state continued for about 5 seconds, so the "melting duration" column was marked "△". Since the "melting point" column was marked "◯", the "void" column was marked "X", and the "melting duration" column was marked "△", the evaluation score for Comparative Example 3 was 3 points.

[0122] Comparative Example 4 was formed by sequentially laminating Cu, Ag, Sn, and Au, and contained 19.6% by weight of Au, 74.8% by weight of Sn, 2.6% by weight of Ag, and 3.0% by weight of Cu.

[0123] FIG. 11(h) is a surface image of Comparative Example 4 during the RTA treatment.

[0124] In Comparative Example 4, the melting point was 210°C, so the "melting point" column was marked with "△", no voids were generated after the RTA treatment, so the "void" column was marked with "◯", and the molten state continued for less than 1 second, so the "melting duration" column was marked with "X". Since the "melting point" column was marked with "△", the "void" column was marked with "◯", and the "melting duration" column was marked with "X", the evaluation score for Comparative Example 4 was 3 points.

[0125] Comparative Example 5 was formed by sequentially laminating Cu, Ag, Sn, and Au, and contained 24.5% by weight of Au, 70.2% by weight of Sn, 2.5% by weight of Ag, and 2.8% by weight of Cu.

[0126] FIG. 11(i) is a surface image of Comparative Example 5 during the RTA treatment.

[0127] In Comparative Example 5, the melting point was higher than 210°C, so the "melting point" column was marked with "x", no voids were generated after the RTA treatment, so the "void" column was marked with "o", and the molten state continued for less than 1 second, so the "melting duration" column was marked with "x". Since the "melting point" column was marked with "x", the "void" column was marked with "o", and the "melting duration" column was marked with "x", the evaluation score for Comparative Example 5 was 2 points.

[0128] Comparative Example 6 was formed by sequentially laminating Cu, Ag, Sn, and Au, and contained 6.9% by weight of Au, 79.0% by weight of Sn, 4.5% by weight of Ag, and 9.6% by weight of Cu.

[0129] FIG. 11(h) is a surface image of Comparative Example 6 during the RTA treatment.

[0130] In Comparative Example 6, the melting point was 210°C, so the "melting point" column was marked "△", a small amount of voids were generated after the RTA treatment, so the "void" column was marked "△", and the molten state continued for 15 seconds or more, so the "melting duration" column was marked "◯". Since the "melting point" column was marked "△", the "void" column was marked "△", and the "melting duration" column was marked "◯", the evaluation score for Comparative Example 6 was 4 points.

[0131] Examples 1, 6, 8, and 9 received a score of 5, and Examples 2 to 5 and 7 received a score of 6. On the other hand, Comparative Examples 1 to 4 received a score of 3, Comparative Example 5 received a score of 2, and Comparative Example 6 received a score of 4.

[0132] Examples 1 to 9 were evaluated to have a score of 5 or more, and Examples 1 to 9 can be used as a solder layer. The composition range in which Examples 1 to 9 are included is a range that contains 7.2 to 14.0% by weight of Au, 0.1 to 4.4% by weight of Ag, 0.1 to 10.1% by weight of Cu, and the remainder consisting of Sn except for unavoidable impurities. A solder layer that contains 7.2 to 14.0% by weight of Au, 0.1 to 4.4% by weight of Ag, 0.1 to 10.1% by weight of Cu, and the remainder consisting of Sn except for unavoidable impurities can be used as a solder layer according to the present application.

[0133] Examples 1 to 5 and 7 were evaluated with a perfect score of 6 points, and Examples 1 to 5 and 7 are optimal as solder layers. The composition range in which Examples 1 to 5 and 7 are included is a range that contains 7.3 wt% to 7.7 wt% Au, 0.1 wt% to 3.1 wt% Ag, 0.5 wt% to 6.7 wt% Cu, and the remainder consisting of Sn except for unavoidable impurities. A solder layer that contains 7.3 wt% to 7.7 wt% Au, 0.1 wt% to 3.1 wt% Ag, 0.5 wt% to 6.7 wt% Cu, and the remainder consisting of Sn except for unavoidable impurities is optimal as a solder layer according to the present application.

[0134] The melting points of Examples 1 to 9 containing 7.2% to 14.0% by weight of Au are 210°C. The solder layer can have a lower melting point by containing 7.2% to 14.0% by weight of Au. The melting points of Examples 1 to 8 containing 7.3% to 14.0% by weight of Au are 205°C. The solder layer can have a further lower melting point by containing 7.3% to 14.0% by weight of Au. Examples 2 to 5, 7 and 8 containing 7.3% to 7.7% by weight of Au have a melting duration of 15 seconds or more. The solder layer can have a melting duration of 15 seconds or more by containing 7.3% to 7.7% by weight of Au.

[0135] The melting points of Examples 1 to 8, which contain 0.1% to 4.4% by weight of Ag and 0.1% to 6.7% by weight of Cu, are 205°C. The solder layer contains 0.1% to 4.4% by weight of Ag and 0.1% to 6.7% by weight of Cu, making it possible to lower the melting point. The melting points of Examples 1 to 7, which contain 0.1% to 3.1% by weight of Ag and 0.1% to 6.7% by weight of Cu, are 205°C, and no voids are generated in Examples 1 to 7. The solder layer contains 0.1% to 3.1% by weight of Ag and 0.1% to 6.7% by weight of Cu, making it possible to lower the melting point, and high reliability is possible without voids being generated.

[0136] In Examples 1 to 9 containing 0.1 wt % or more and 10.1 wt % or less of Cu, a large amount of voids does not occur. By containing 0.1 wt % or more and 10.1 wt % or less of Cu, the solder layer can be made highly reliable. In Examples 1 to 7 and 9 containing 0.1 wt % or more and 10.1 wt % or less of Cu and 0.1 wt % or more and 3.1 wt % or less of Ag, no voids occur. By containing 0.1 wt % or more and 10.1 wt % or less of Cu and 0.1 wt % or more and 3.1 wt % or less of Ag, the solder layer can be made even more reliable. [Explanation of symbols]

[0137] 1~4 Thin films for semiconductor laser bonding 10 Submount substrate 20 electrode layer 30, 31 Diffusion prevention layer 40, 45 solder layer 41 Cu layer 42 Ag layer 43 Sn layer 44 Au layer

Claims

1. A solder layer containing 7.2 wt % or more and 14.0 wt % or less of Au, 0.1 wt % or more and 4.4 wt % or less of Ag, 0.1 wt % or more and 10.1 wt % or less of Cu, and the remainder being Sn except for unavoidable impurities. A thin film for semiconductor laser bonding, characterized in that

2. 2. The semiconductor laser bonding thin film according to claim 1, wherein Cu forms a Cu layer disposed over the entire surface of one surface of the solder layer.

3. 3. The thin film for semiconductor laser bonding according to claim 1, containing 7.3% by weight to 14.0% by weight of Au.

4. 3. The thin film for semiconductor laser bonding according to claim 1, containing 0.1 to 4.4 wt % of Ag and 0.1 to 6.7 wt % of Cu.

5. 3. The thin film for semiconductor laser bonding according to claim 1, containing 0.1 to 10.1 wt % of Cu and 0.1 to 3.1 wt % of Ag.

6. 3. The thin film for semiconductor laser bonding according to claim 1 or 2, wherein the solder layer contains 7.3 wt % or more and 7.7 wt % or less of Au, 2.9 wt % or more and 3.1 wt % or less of Ag, and 0.5 wt % or more and 6.7 wt % or less of Cu.

7. 3. The thin film for semiconductor laser bonding according to claim 1, further comprising a diffusion prevention layer containing Pt and disposed so as to face the surface of the solder layer on which the Cu is disposed.

8. 8. The semiconductor laser bonding thin film according to claim 7, wherein the diffusion prevention layer has a Cr layer containing Cr and a Pt layer containing Pt and disposed between the Cr layer and the solder layer.

9. 1. A method for manufacturing a thin film for semiconductor laser bonding, comprising a solder layer containing 7.2 wt % or more and 14.0 wt % or less of Au, 0.1 wt % or more and 4.4 wt % or less of Ag, 0.1 wt % or more and 10.1 wt % or less of Cu, and the remainder being Sn except for unavoidable impurities, comprising: A Cu layer is formed, forming an Ag layer on the Cu layer; forming a Sn layer on the Ag layer; forming an Au layer on the Sn layer; 2. A method for producing a thin film for semiconductor laser bonding, comprising the steps of:

Citation Information

Patent Citations

  • Semiconductor device and its manufacturing method, and member for semiconductor device

    JP2007288001A